OPTIMIZINg INTERNAL HUMAN RELATION OF LEADER IN IMPROVINg ORgANIZATIONAL PERFORMANCE - Laela Fitrotus Zahroh; Olivia Fachrunnisa (UNISSULA, 2017)
This study aimed to figure out and analyzes the factors that support and impede the internal human relations of school principals in improving organizational performance; the effort of principals to overcome obstacles of internal human relations in improving organizational performance; and design an optimization model of internal human relations done by principal in improving organizational performance. This study was conducted on three SMA Negeri (State Senior High School) in Jepara. This research used purposive sampling technique. Data collection techniques was done by interview techniques. Data analysis technique was done by using credibility test with triangulation model. Data analysis was by using thematic data analysis. The results showed that the factors that support organizational performance are factors of internal human relations quality in the form of openness, supportiveness and mutual trust, dyadic and small group relationship and the use of communication tools to facilitate communication if it cannot meet face to face directly. To optimize Internal human relations, it can be done through improving openness, mutual support (supportiveness) and the sense of equality between the leaders and members. In improving the performance of the organization, it can also be done through direct and indirect communication. Direct communication is done persuasively. While indirect communication is communication by using communication tool. Internal human relation is also can be done through dyadic communications, regular communications and small group relationship in the form of briefing.Keywords: internal human relations, interpersonal communication, principal, organizational performance